Executive compensation tied to ESG performance: International evidence - Shira Cohen; Igor Kadach; Gaizka Ormazabal; Stefan Reichelstein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
This paper examines the reliance on ESG metrics in executive compensation contracts. In our sample of international publicly traded firms, a rapidly growing fraction incorporate ESG metrics in the compensation schemes of their top executives. Our analysis links the reliance on these metrics to firm fundamentals, the geographic location of firms, as well as the influence of institutional shareholders. Our findings also suggest that the adoption of ESG variables in managerial performance measures is accompanied by improvements in ESG performance and meaningful changes in the compensation of executives.
Keywords: M12; M41; Q54; 330; ESG metrics; Executive compensation; Institutional ownership